2017
DOI: 10.1007/s10815-017-0983-6
|View full text |Cite
|
Sign up to set email alerts
|

Replacing single frozen-thawed euploid embryos in a natural cycle in ovulatory women may increase live birth rates compared to medicated cycles in anovulatory women

Abstract: Natural FET in ovulatory women after IVF-PGS is associated with increased implantation and live birth rates compared to programmed FET in anovulatory women. Further investigation is needed to determine whether these findings hold true in other patient cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Melnick et al compared pregnancy outcomes between natural cycle FET and aFET in patients undergoing euploid blastocyst transfers. They reported that implantation, clinical, and ongoing pregnancy rates were found to be significantly higher in ovulatory patients undergoing the natural cycle FET as compared to aFET for anovulatory patients [37]. In accordance with the previous study, our ongoing pregnancy rate and live birth rate were higher in Ovu-FETs and the miscarriage rate was significantly lower.…”
Section: Afet Vs Ovu-fetsupporting
confidence: 89%
“…Melnick et al compared pregnancy outcomes between natural cycle FET and aFET in patients undergoing euploid blastocyst transfers. They reported that implantation, clinical, and ongoing pregnancy rates were found to be significantly higher in ovulatory patients undergoing the natural cycle FET as compared to aFET for anovulatory patients [37]. In accordance with the previous study, our ongoing pregnancy rate and live birth rate were higher in Ovu-FETs and the miscarriage rate was significantly lower.…”
Section: Afet Vs Ovu-fetsupporting
confidence: 89%
“…The decision to perform a medicated prepared cycle or a natural cycle has largely been based on physician and patient preference as there is conflicting data on the benefit of one compared with the other. Three retrospective analysis showed a benefit in performing frozen embryo transfers in natural cycles compared with medicated prepared cycles [ 4 6 ], while other retrospective analysis have shown no difference [ 7 , 8 ]. Groenewoud et al performed a prospective non-inferiority randomized controlled trial and found a non-inferior live birth rate in medicated prepared cycles compared with modified natural frozen embryo transfers.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies suggest better outcomes with regards to clinical (19,(33)(34)(35)(36)(37), ongoing (19,33,(38)(39)(40), and live birth (18,19,33,34,(36)(37)(38)(40)(41)(42)(43) rates in (modified) natural or stimulated FET cycles compared to cycles performed in an artificial setting. Nevertheless, these data are from different populations and quality and mainly from retrospective observational studies which prompts caution when drawing conclusions for clinical practice.…”
Section: Discussionmentioning
confidence: 99%